Criminal organization offenses in the Peruvian Criminal Code - Prado Saldarriaga, Víctor Roberto (2019)
The paper carries out a dogmatic revision of the crimes of «criminal organization», provided for in Section 317 of the Peruvian Criminal Code of 1991, and of «criminal gang», described in Section 317-B of the same Code, in order to establish and explain the functions and differences that underlie the plurality of legal provisions that seek to regulate the criminal relevance of criminal organizations. Likewise, it analyzes the doctrinal, legislative and jurisprudential contributions that seek to delimit, with extreme precision, the characteristics, effects, and normative components of both criminal types and the catalog of specific aggravating circumstances, in order to finally make recommendations on their current regulation that promotes the necessary legislative amendments to overcome the difficulties and inconsistencies, both theoretical and practical, of said criminal provisions.